Modelling single-molecule kinetics of helicase translocation using high-resolution nanopore tweezers (SPRNT). Issue 1 (16th April 2021) - Craig, Jonathan M.; Laszlo, Andrew H.; Nova, Ian C.; Gundlach, Jens H.
Abstract: Single-molecule picometer resolution nanopore tweezers (SPRNT) is a technique for monitoring the motion of individual enzymes along a nucleic acid template at unprecedented spatiotemporal resolution. We review the development of SPRNT and the application of single-molecule kinetics theory to SPRNT data to develop a detailed model of helicase motion along a single-stranded DNA substrate. In this review, we present three examples of questions SPRNT can answer in the context of the Superfamily 2 helicase Hel308. With Hel308, SPRNT's spatiotemporal resolution enables resolution of two distinct enzymatic substates, one which is dependent upon ATP concentration and one which is ATP independent. By analyzing dwell-time distributions and helicase back-stepping, we show, in detail, how SPRNT can be used to determine the nature of these observed steps. We use dwell-time distributions to discern between three different possible models of helicase backstepping. We conclude by using SPRNT's ability to discern an enzyme's nucleotide-specific location along a DNA strand to understand the nature of sequence-specific enzyme kinetics and show that the sequence within the helicase itself affects both step dwell-time and backstepping probability while translocating on single-stranded DNA.